Ground spiders (Araneae: Gnaphosidae, Liocranidae, Prodidomidae) from the Greek islands Rodos, Symi and Karpathos, with the description of new species - Chatzaki, Maria; van Keer, Johan (Zootaxa, 2019)
New taxonomic data on the ground spiders of the families Gnaphosidae, Liocranidae and Prodidomidae from the Greek islands Rodos and Symi are presented resulting from extensive field work conducted in 2006. Additional material from Karpathos is also included. In total, 48 species are recorded, and five new species (Drassodes mylonasi Chatzaki sp.n., Echemus kaltsasi Chatzaki sp.n., Minosiella apolakia Chatzaki sp.n., Phaeocedus vankeeri Chatzaki sp.n., and Turkozelotes attavirus Chatzaki sp.n.) are proposed. Although the Gnaphosidae of Cyprus are not the focus of the present paper, the unknown female of Echemus levyi Kovblyuk, 2009 found in Cyprus, is also described here for comparative purposes. Leptodrassex memorialis (Spassky, 1940) is justifiably transferred to the genus Leptopilos Levy, 2009 and it is therefore regarded as Leptopilos memorialis comb.nov. The male of Zelotes daidalus Chatzaki, 2003 and the female of Z. minous Chatzaki, 2003 are newly matched and Z. daidalus is further synonymised with Z. shaked Levy, 1998.The new matching of Z. minous males with Z. daidalus females is justified. Two species are new records for Greece: Zelotes limnatis Chatzaki & Russell-Smith, 2017 and Agraecina scupiensis Deltshev, 2016.